The impact of pre-hospital emergency medical services on the outcomes of patients with burn: a systematic review and meta-analysis - Ahmed Alanazy; Abdullah Alruwaili (Emergency Care Journal)
Burn injuries are a worldwide health issue, significantly burdening healthcare facilities. Specialized burn centres are only sometimes available near the site of burn injury. First aid greatly impacted the outcomes of burns by evaluating the severity of the burn and associated injuries. Pre-hospital Emergency Medical Services (EMS) have more remarkable contributions to healthcare systems. We aimed to reveal the interventions provided by the EMS staff on the scene of burn injuries and the impact of these interventions on the outcomes of burn injuries. Furthermore, the study aimed to identify areas for improvement in pre-hospital burn care. A systematic literature review was carried out from inception to 1st July 2023 using twelve databases. All original articles that included patients with burn injuries who received the necessary pre-hospital care by EMS staff were included. Nine articles comprehending 6149 patients with burn injuries were retrieved. The analysis revealed that EMS interventions significantly improved  the outcomes of burn management. This included better control for pain and vital parameters, and lower mortality risk. The EMS provided analgesic administration, cooling of the burn wound, and the necessary urgent therapies.  However, the study identified a need for better EMS training in assessing burn severity and managing burn injuries effectively. Enhancing EMS providers' knowledge and skills in pre-hospital burn management could substantially improve patient outcomes and reduce the burden on healthcare systems. Improving the understanding of EMS providers towards burn care can minimize the risk of burn-related poor outcomes and reduce the burden on healthcare facilities.